Pengaruh Service Quality dan Tingkat Religiusitas terhadap Minat Menabung di Bank Syariah Indonesia - Rayhan Ahmadi; Siswanto Siswanto (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of service quality and level of religiosity on the intention to save at Islamic banks in Indonesia. This study uses a quantitative descriptive research method. The sample used was 140 respondents (15 question items x 5) referring to Malhotra's theory and the sample in this study were UIN Malang students. The tests were carried out using the statistical package for the social sciences (SPSS). The sampling technique in this study used purposive sampling. The results of this study indicate that the effect of service quality and the level of religiosity partially and simultaneously has a significant effect on the intention to save at Islamic banks in Indonesia.